profile
Опубликовано 2 года назад по предмету Алгебра от asvista

 

Упростите выражение

  1. Ответ
    Ответ дан GodzillAMC

    frac{sqrt{2}*cosalpha-2(cos45*cosalpha+sin45*sinalpha)}{2*(sin30*cosalpha+cos30*sinalpha)-sqrt{3}sinalpha}= frac{sqrt{2}*cosalpha-sqrt{2}*cosalpha-sqrt{2}*sinalpha}{cosalpha+sqrt{3}*sinalpha-sqrt{3}*sinalpha}=frac{sqrt{2}*sinalpha}{cosalpha} =sqrt{2}tgalpha

  2. Ответ
    Ответ дан ConsuLX

    (V2cosa-2cos(45-a))/(2sin(30+a)-V3sina)=(V2cosa-V2cosa-V2sina)/(cosa+V3sina-V3sina)=(V2sina)/(cosa)=V2tga

     

    V - квадратный корень

     

Самые новые вопросы